A One-Stop Protocol to Assess Myocardial Fibrosis in Frozen and Paraffin Sections - Divya Sridharan; Nooruddin Pracha; Julie A. Dougherty; Ali Akhtar; Syed Baseeruddin Alvi; Mahmood Khan (Methods and Protocols, 2022)
Masson’s Trichrome Staining (MTS) is a useful tool for analyzing fibrosis in a plethora of disease pathologies by differential staining of tissue components. It is used to identify collagen fibers in different tissues like heart, lung, skin, and muscles. Especially in cardiac fibrosis, MTS stains the collagen fibers (blue color), which helps in the distinction of scar area versus the healthy area (red color). However, there are several challenges to stain both paraffin-embedded sections and frozen (cryosections) using a single protocol. Therefore, the goal of this study was to develop a simple short protocol to assess cardiac fibrosis in both paraffin-embedded and cryo heart sections. MTS uses three different stains, i.e., Weigert’s Iron Hematoxylin, Biebrich scarlet-acid fuchsin, and aniline blue to detect nuclei, cytoplasm, and collagen, respectively. In this study, we developed a simple short protocol that can be adapted by any lab to easily assess cardiac fibrosis in paraffin and frozen heart sections. Furthermore, we have addressed the challenges that are commonly faced during the immunostaining process and troubleshooting techniques. Overall, we have successfully developed a simple one-step protocol to assess myocardial fibrosis in paraffin-embedded and frozen cryosections.